FINANCIAL ANALYSIS OF PIG LIVESTOCK BUSINESS WITH VARIOUS TYPES OF RANSUM (Case Study of Pig Farming in Jadi Village Tabanan Regency) - Wiranata G. A.; B. R. T. Putri; D. A. Warmadewi (Fakultas Peternakan Universitas Udayana, 2020)
The purpose of this study was to analyze the income of pig farm by replacing pollard treatment with rice bransupplemented with multiple mineral vitamins. The design used was a randomized block design (RBD) consisting of 4 treatments and 4 groups as replications, grouping based on body weight of pigs. The treatments used were rations using commercial concentrate and pollard (A) as controls, TBN-01 concentrate rations and pollard (B), TBN-01 concentrate rations and rice bran (C), TBN-01 concentrate rations and rice bran with mutli mineral vitamin supplementation pignox (D). The research variables are (1) management of pig husbandry management including selection of seeds, housing, feeding, labor, animal health and marketing. (2) financial analysis of pig fattening business includes total cost, revenue, profit, R/C ratio (revenue and cost ratio), BEP (Break Event Point). The results showed that based on the total cost, the business of pig farming with pollard replacement treatment with rice bran supplemented with multi mineral vitamins amounted to 0,20% (D) resulting in the largest R/C ratio of 1,51 or a percentage of profit of 51%. The conclusion of this study is that with good maintance management seen from body weight gain in treatment D of 23,75 g/head with an R/C ratio of 1,51 and lowering production cost by 1,51%.